Предмет: Алгебра, автор: nadezdaminenkova6

Решите пж
1) (x+y-xy^2)x^2y=
2) (4-x)2x=
3) (x+2)(4-x)=
4) (y^2+3)(7-y)
5) 32m^9×m^3-m×0,5m^4+3m^2-24×0,2m-n×0,4+14-14m^2×m^1 0


nadezdaminenkova6: Решите пж, буду благодарна

Ответы

Автор ответа: aastap7775
1

1. (x+y-xy^2)x^2y = x^3y + x^2y^2 - x^3y^3\\2. (4-x)2x = 8x - 2x^2\\3. (x+2)(4-x) = -x^2 + 2x + 8\\4. (y^2+3)(7-y) = -y^3 + 7y^2 - 3y + 21\\5. 32m^9*m^3 - m*0.5m^4 + 3m^2-24*0.2m-n*0.4+14-14m^2*m^{10} = 32m^{12} - \frac{1}{2}m^5 + 3m^2 - 4.8m - 0.4n +14 - 14m^{12} = 18m^{12} - 0.5m^5 + 3m^2 - 4.8m - 0.4n + 14

Похожие вопросы
Предмет: Математика, автор: волалпалал